Epiphytic Communities On Posidonia Oceanica (L.) Delile Leaves Along The North Tyrrhenian Coasts (N.W. Mediterranean Sea, Italy) - BEDINI, R.; CANALI, M.G.; BERTUCCELLI, M. (Mediterranean Marine Science, 2003)
The structure of epiphytic communities was studied from February to November 2000 at three different levels (upper limit, lower limit, central zone) in depth (- 5 to – 26 m) in five Posidonia oceanica(L.) Delile 1813 Tuscany coast meadows: Rosignano, San Vincenzo, Piombino, Punta Ala, Portoferraio (Isle of Elba). The study was focused on leaf epiphytes and epifauna. Three shoots in three plots were collected randomly in each area (nine shoots per area) in each site of each meadow. A quantitative description of the epiphytes and epifauna was carried out, regarding the three groups: Algae, Hydroids and Bryozoans, both on the outer and the inner surfaces of the leaf blade. The dynamics of communities of the leaf-stratum along a bathymetric gradient showed a seasonal variation characterized by the highest richness of epiphytes mainly in the upper limit, especially in early spring. Significant differences were demonstrated for the epiphytic communities of the external leaf-stratum both on the upper and the central limit of the studied meadows.